"A counterfeit friendship": mate crime and people with learning disabilities. Issue 6 (2nd December 2014) - Andrew Landman, Roderick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to offer an introduction to the recently recognised phenomenon of "mate crime" as it affects people with learning disabilities. It looks at how concerns arose, considers what may make people with learning disabilities particularly susceptible, and proposes a provisional definition of "mate crime". Design/methodology/approach – The paper draws on the author's own project work, and reviews the extant research literature on "disablist" hate crime to examine the extent to which so-called "mate crime" has been both explicitly and implicitly identified and analysed in the literature. Findings – The literature review indicates that "mate crime" has not been explicitly identified in any scholarly research to date, either under that or any other name. Crimes that we might label as "mate crimes" have, however, appeared in more general literature concerning the experiences of people with disabilities in general, and as victims of crime. Social implications – Despite a lack of firm data there is sufficient in the literature, combined with increasing anecdotal evidence and case studies, to suggest that people with learning disabilities are particularly susceptible to "mate crime", and are being targeted by perpetrators. Increasing independence and reduced service provision are likely to increase the risks. The author argues that mate crime differs significantly from other manifestations of hate crime and abuse, and needs to be conceptualised, analysed and handled differently. Originality/value – Whilst the issue of "mate crime" is gaining increasing professional and media attention it lacks any academic base and a definition. This paper attempts to establish an agreed definition and conceptualisation of "mate crime".